Effect of plyometric training program on speed and dynamic balance performances in volleyball players - Güzelsoy Kanbak, C.; Daglioglu, Ö. (European Journal of Physical Education and Sport Science, 2020)
The aim of this study is to examine the effect of plyometric training program on speed and dynamic balance performance of volleyball players. Twenty male volleyball players aged 18-23, who do regular volleyball training, participated in the study voluntarily. The subjects were randomly divided into two different groups as the experimental group (n = 10, age: 20.54 ± 2.14) and the control group (n = 10, age: 21.62 ± 2.17). The experimental group performed a plyometric training program 3 days a week for 8 weeks. Both groups continued their normal volleyball training. Exercises known as drop jump, box jump, squat jump, split squat jump, overhead slam and plyometric push-ups were applied to the experimental group. Speed (30 m) and dynamic balance measurements were made before and after the training started. Biodex Balance SD Isokinetic Balance Test was applied for dynamic balance measurement. Paired Sample t test was used for in-group comparisons for statistical analysis of the data, and Independent Sample t test was used for intergroup comparisons. The level of significance was set at p<0.05. When the pre-test and post-test measurements of the experimental group were examined, a significant difference was found in dynamic balance scores (p<0.05). There was no significance in the speed data (p>0.05). When the pre-test and post-test measurements of the groups were compared, a significance was observed in the right leg and left leg general dynamic balance scores in favor of the experimental group (p<0.05). As a result, it can be said that the plyometric training program applied to volleyball players improves the speed and dynamic balance scores.